Development of spectrum management tool for Malaysia using open-source GIS software - Saman, Mohamad Afif; Ismail, Ahmad Fadzil; Badron, Khairayu; Mohd. Ramli, Huda Adibah; Hashim, Wahidah; Fakrullah, Ahmad Nasruddin ’Atiqullah (Springer International Publishing, 2015)
The mobile communication technology growth in Malaysia, particularly in cellular network has led to higher demand of spectrum access. However, with limited number of radio spectrum availability, an effective spectrum management tool is needed. The commercial software will be an expensive solution for a long run in the rapidly changing environment of mobile technologies. Hence the development of open-source spectrum management tool that not only efficient but also cost effective is needed. The tool must be able to manage existing spectrum and assist in spectrum planning for new base station (BS). It also must be able to identify possible interference that could happen between BS. This paper will highlight the development of spectrum management tool using open-source resources for Malaysian authority. The simple cost effective tool is able to do proper spectrum management and planning for 2G, Global System for Mobile Communications (GSM), and 3G, Universal Mobile Telecommunications System (UMTS) networks.